2015
DOI: 10.12659/msm.893754
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Bmi-1 Gene Enhances Chemotherapy Sensitivity in Human Glioblastoma Cells

Abstract: BackgroundThe aim of this study was to determine the influence of the BMI1 gene on chemotherapy sensitivity in human glioma cells.Material/MethodsThe expression of the BMI1 gene in 41 cases of human brain glioma was determined by quantitative real-time PCR. The silencing effect of RNA interference on the BMI1 gene was detected by Western blot. Methyl thiazolyl tetrazolium assay (MTT) and flow cytometry methods were used to determine the cell viability and apoptosis rate of the U251 cells with BMI1 silencing. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…High levels of therapy resistance, strong cellular invasiveness, and rapid cell growth demand aggressive multimodal therapies involving resection followed by radio-chemotherapy [ 2 , 3 ]. Although the treatment strategies have been improved remarkably, including surgical equipment or adjuvant therapy, the overall survival rate of GBM is still very poor and new therapies are urgently needed [ 4 6 ]. The finding of new biomarkers can help discover new targeted drugs and therapies.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of therapy resistance, strong cellular invasiveness, and rapid cell growth demand aggressive multimodal therapies involving resection followed by radio-chemotherapy [ 2 , 3 ]. Although the treatment strategies have been improved remarkably, including surgical equipment or adjuvant therapy, the overall survival rate of GBM is still very poor and new therapies are urgently needed [ 4 6 ]. The finding of new biomarkers can help discover new targeted drugs and therapies.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the silencing of BMI-1 may significantly inhibit A-431 cell proliferation through the promotion of apoptosis. Numerous studies have revealed that BMI-1 has a role in tumor development, invasion and metastasis ( 11 14 , 18 ). Destruction of the extracellular matrix and migration into the vascular system are key steps required for tumor metastasis ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that BMI-1 expression, which is upregulated in multiple types of cancer, is positively correlated with clinical grade/stage and poor prognosis in cervical ( 7 ), ovarian ( 8 ), endometrial ( 9 ) and lung ( 10 ) cancer. Silencing of BMI-1 expression by RNA interference (RNAi) has been observed to decrease the rate of tumor cell growth, resulting in cell cycle arrest and inhibition of the invasive ability of tumor cells ( 11 14 ). In the present study, BMI-1 expression in VSCC was examined, and the effect of small-interfering RNA (siRNA)-mediated silencing of BMI-1 in A-431 cells was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition, silencing of Bmi-1 gene led to the increased chemotherapy sensitivity of human glioblastoma (GBM) cells, and a specific inhibitor of Bmi-1, PTC-209, could significantly attenuate the glioblastoma growth in murine orthotopic xenograft model. 19,20 In consideration of PCGF1 associated with nervous system development, we were very interested in its expression and its functions in a nervous system tumor. To the best of our knowledge, there are only a few studies till date on the therapeutic potential and regulation mechanism of PCGF1 in glioblastoma (GBM) cell lines.…”
Section: Introductionmentioning
confidence: 99%